Efecto del ácido indolbutírico (IBA) y 6-bencilaminopurina (BAP) en el desarrollo in vitro de yemas axilares de Encyclia microtos (Rchb.f.) Hoehne (Orchidaceae) - Condemarín-Montealegre, Carlos (Universidad de Costa Rica, 2015)
Encyclia microtos (Rchb.f.) Hoehne, is an endemic orchid that are distributed in the north of Peru (Tumbes and Piura) and it is being depredy illegally causing the extinction of the same one. With inter- est to maintain his conservation, is an alternative by means of the propagation in vitro. For that reason the objective of this research is to evaluate the indolbutiric acid effect (AIB) and 6-bencilaminopurine (BAP) in the development in vitro of axillar bud of E. microtos. The experience with plant of 120 days of age began, it was introduced in medium MS (Murashige and Skoog) suplement with sucrose, phytagel, AIB , BAP (sin- gle or combined) and adjusting to pH of 5.5. Nine treatments were made, in a rank of 0; 1 and 2 ppm (sin- gle or combined). The results showed that BAP (2 ppm) promoted the greater development of axillary buds with a rate of multiplication of the double of plant to the 90 days in which they were exposed to the growth regulators. To single concentrations of AIB (1 ppm and 2 ppm), promoted a better development of leaves, roots and length of the same ones.